Accelerated corrosion testing of cold spray coatings on 304L in chloride environments - Karasz, Erin K.; Montoya, Timothy D.; Taylor, Jason M.; Ross, Kenneth A.; Schaller, Rebecca F. (Frontiers in Metals and Alloys, 2022)
Cold spray is an advanced metal manufacturing technique applied across many fields for a wide range of functions. Low heat input and compressive stresses induced into the substrate by the cold spray process makes it a promising choice for protective corrosion resistant coatings. One potential application for cold spray is as a protective coating against corrosion for spent nuclear fuel (SNF) interim dry storage canisters. As these canisters are currently stored at interim storage locations longer than originally intended, chloride induced stress corrosion cracking has been identified as a high priority knowledge gap, specifically with respect to prolonging or extending canister lifetimes(1). The high deployability of cold spray, for which nozzles have been developed for application in constrained spaces, in conjunction with beneficial properties inherent to cold spray makes this a good candidate for a corrosion protection coating on SNF canisters. This work explores a pathway to rapidly down-select cold spray coatings for canisters by focusing on the corrosion properties. Specifically, this study examines the corrosion protection abilities of nickel and nickel-based alloy cold spray coatings on 304L stainless steel in chloride rich environments through electrochemical scans and ferric chloride pitting tests (ASTM G48 Method A). It was shown that the porosity of the coating, the processing gas, material selection, and deformation in the substrate all impact the corrosion behavior of cold spray coatings and are areas where optimization could reduce potential materials degradation, enabling enhanced coatings development.